2017
DOI: 10.1103/physreva.95.012502
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of large effective electric fields of weakly polar molecules for electron electric-dipole-moment searches

Abstract: The electric dipole moment of an electron (eEDM) is one of the sensitive probes of physics beyond the standard model. The possible existence of the eEDM gives rise to an experimentally observed energy shift, which is proportional to the effective electric field (E eff ) of a target molecule. Hence, an analysis of the quantities that enhance E eff is necessary to identify suitable molecules for eEDM searches. In the context of such searches, it is generally believed that a molecule with larger electric polariza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
7
13
0
Order By: Relevance
“…al. studied large eEDM enhancement effects in hydrides within orbital interaction theory and remarked an influence of the energy difference between the interacting valence orbitals of the electronegative atom and the unoccupied p 1/2 orbital of the heavy atom [14]. Both of the mentioned studies confirmed that large contributions of s-and p-type atomic orbitals in the singly occupied molecular orbital increase P, T -odd effects, as expected [12].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…al. studied large eEDM enhancement effects in hydrides within orbital interaction theory and remarked an influence of the energy difference between the interacting valence orbitals of the electronegative atom and the unoccupied p 1/2 orbital of the heavy atom [14]. Both of the mentioned studies confirmed that large contributions of s-and p-type atomic orbitals in the singly occupied molecular orbital increase P, T -odd effects, as expected [12].…”
Section: Introductionsupporting
confidence: 66%
“…For comparison, instead of the improved relativistic factor for W s (eq. (18)) relation (14) can be used to receive relativistic enhancement factors:…”
Section: B Scaling-relations Of P T -Odd Propertiesmentioning
confidence: 99%
“…21,22 The theoretical search for still more favourable candidates for eEDM experiments, employing relativistic quantum chemistry, is vivid. [23][24][25][26][27][28][29][30] So far, besides the strong Z-dependence of CP-violating effects, there appears to be no thorough understanding of the mecha-nisms that make eEDM enhancement in molecular systems large, but first attempts in this direction have been reported recently 31 . Thus, a systematic study of P, T -odd effects in molecules is of avail.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in Ref. [41], the reason for the high value of the P, T molecular parameter in HgH was discussed using the Mulliken population analysis and the orbital interaction theory. The authors of the Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the Ref. [41] claimed that the large s-p mixing in the singly occupied molecular orbital increases the effective electric field in a molecule. Thus, large s-p mixing may be one of the reasons for the exceptionally high magnitude of the P, T -odd molecular parameters in HgH.…”
Section: Resultsmentioning
confidence: 99%